The Receptivity of Career Practitioners Toward Career Development Resources on the Internet - Hambley, Laura A.; Magnusson, Dr. Kris (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this study was to explore the receptivity of career practitioners toward career development resources on the Internet. The knowledge, skills, and attitudes of 102 career practitioners toward career development Internet resources were assessed through a researcher-designed survey. Results demonstrated that career practitioners are generally receptive toward career development resources on the Internet; they reacted somewhat positively toward the Internet, and are beginning utilize it. However, there are still a number of concerns that must be alleviated before career practitioners will make greater use of the Internet, most of which can be dealt with through practice and training.